2012
DOI: 10.1093/nar/gks1186
|View full text |Cite
|
Sign up to set email alerts
|

SpermatogenesisOnline 1.0: a resource for spermatogenesis based on manual literature curation and genome-wide data mining

Abstract: Human infertility affects 10–15% of couples, half of which is attributed to the male partner. Abnormal spermatogenesis is a major cause of male infertility. Characterizing the genes involved in spermatogenesis is fundamental to understand the mechanisms underlying this biological process and in developing treatments for male infertility. Although many genes have been implicated in spermatogenesis, no dedicated bioinformatic resource for spermatogenesis is available. We have developed such a database, Spermatog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 36 publications
3
25
0
Order By: Relevance
“…S7), and it is interesting that 83 of the 117 (ϳ71%) phosphorylated substrates were enriched in both IMAC and TiO 2 . Although PLKs were not annotated as spermatogenesis-related in the gene ontology database (40) or SpermatogenesisOnline database (43), a number of spermatogenesis-related proteins were predicted to be regulated by PLKs in our study. The PLK-regulated spermatogenesis-related sub-KSPN is presented in Fig.…”
Section: Prediction Of Kinases With Differential Activities In Order mentioning
confidence: 69%
“…S7), and it is interesting that 83 of the 117 (ϳ71%) phosphorylated substrates were enriched in both IMAC and TiO 2 . Although PLKs were not annotated as spermatogenesis-related in the gene ontology database (40) or SpermatogenesisOnline database (43), a number of spermatogenesis-related proteins were predicted to be regulated by PLKs in our study. The PLK-regulated spermatogenesis-related sub-KSPN is presented in Fig.…”
Section: Prediction Of Kinases With Differential Activities In Order mentioning
confidence: 69%
“…Detailed analysis further showed that eight genes are essential for spermatogonia proliferation, 78 genes are essential for meiosis, and 141 genes are essential for spermatogenesis (Supporting Information Data 6). We further downloaded human spermatogenesis‐associated genes from SpermatogenesisOnline 1.0 and obtained a list of 322 human Ensembl genes . A total of 134 macaque testis genes have one‐to‐one orthologs with human spermatogenesis‐associated genes (Supporting Information Data 2).…”
Section: Resultsmentioning
confidence: 99%
“…S1 B). GPS1, HID1, and USP36 are annotated ubiquitously expressed in various tissues (Zhang et al, 2013; DNAH17 mRNA exhibits testis-specific expression [Milisav and Affara, 1998]). Given that our patients did not show any other symptoms except asthenozoospermia, the homozygous missense variant (c.G5408A) in DNAH17 was favorably presumed to be responsible for the diminished sperm motility in the patients.…”
Section: Identification Of a Candidate Pathogenic Variant In Dnah17mentioning
confidence: 99%
“…(2) variants with minor allele frequencies >0.05, suggested by American College of Medical Genetics and Genomics for benign mutations (Richards et al, 2015), in any of the public databases, 1000 Genome project (Auton et al, 2015), ESP6500 (Fu et al, 2013), or ExAC database (Lek et al, 2016), and variants homozygous in our in-house WES variants call set generated from 578 fertile male samples (41 Pakistanis, 254 Chinese, and 283 Europeans) were excluded; (3) variants potentially affecting protein sequence and (4) in genes expressed in testis based on Sperma-togenesisOnline1.0 (https://mcg.ustc.edu.cn/bsc/spermgenes/; Zhang et al, 2013) were kept; (5) variants predicted to be deleterious by less than half of the 13 software (Adzhubei et al, 2010;Choi et al, 2012;Chun and Fay, 2009;Davydov et al, 2010;Dong et al, 2015;Lindblad-Toh et al, 2011;Reva et al, 2011;Schwarz et al, 2014;Shihab et al, 2013;Shihab et al, 2015;Sim et al, 2012) covering them were excluded; (6) variants in genes for which inactivation has no effects on male fertility or spermatogenesis based on Spermatogenesi-sOnline1.0 (Zhang et al, 2013) were excluded; (7) the remaining variants were subsequently detected by Sanger sequencing in all the family members available (III:1, III:2, and IV:1-7). Fig.…”
Section: Filtering Of Candidate Variantsmentioning
confidence: 99%